Strategi Menaikan Kinerja Guru dalam Online Learning di Era Social Distancing - Andi Sulistiadi; Otto Berman Sihite; Virza Utama Alamsyah (Kelola: Jurnal Manajemen Pendidikan, 2020)
The Covid-19 pandemic has a profound impact on the world of education. Online learning (KBM) is a process that must be done. This study aimed to prove a number of HR variables that affects the teachers’ performance in the online learning era. In this era, it is believed that the role of teachers as a children educator even the face-to-face is irreplaceable by these digital tools. It turns out that the teacher who performs well is not merely motivated by payroll and bonuses, but there are other aspects that determine the good performance. This study was conducted at Pelita Harapan Bangsa Tegal. The population was 57 teachers and data collection techniques used in this study by distributing questionnaire, and the data were analyze with Smart PLS version 3.0. The result showed that HR variable consisting of Work discipline, Organization commitment and the Work Environment that positively influences teacher performance. HR Strategies have positive effects such as: disciplining in all levels, expressed and fulfilled organizational commitment, as well as work environment that is designed as comfortable as possible for teachers to improve their performance.